Is Osteogenic Differentiation of Human Nucleus Pulposus Cells a Possibility for Biological Spinal Fusion?. (April 2020) - Brown, Sharon J.; Turner, Sarah A.; Balain, Birender S.; Davidson, Neil T.; Roberts, Sally
Objective: The purpose of this study was to investigate whether a simple, biologically robust method for inducing calcification of degenerate intervertebral discs (IVD) could be developed to provide an alternative treatment for patients requiring spinal fusion. Design: Nucleus pulposus (NP) cells isolated from 14 human IVDs were cultured in monolayer and exposed to osteogenic medium, 1, 25-dihydroxyvitamin D3 (VitD3 ), parathyroid hormone (PTH), and bone morphogenic proteins (BMPs) 2/7 to determine if they could become osteogenic. Similarly explant cultures of IVDs from 11 patients were cultured in osteogenic media with and without prior exposure to VitD3 and BMP-2. Osteogenic differentiation was assessed by alkaline phosphatase activity and areas of calcification identified by alizarin red or von Kossa staining. Expression of osteogenic genes during monolayer culture was determined using polymerase chain reaction and explant tissues assessed for BMP inhibitors. Human bone marrow–derived mesenchymal stromal cells (MSCs) were used for comparison. Results: Standard osteogenic media was optimum for promoting mineralization by human NP cells in monolayer. Some osteogenic differentiation was observed with 10 nM VitD3, but none following application of PTH or BMPs. Regions of calcification were detected in 2 of the eleven IVD tissue explants, one cultured in osteogenic media and one with the addition of VitD3 and BMP-2. Conclusions: Human NP cells can become osteogenic in monolayer and calcification of the extracellular matrix can also occur, although not consistently. Inhibitory factors within either the cells or the extracellular matrix may hinder osteogenesis, indicating that a robust biological fusion at this time requires further optimization.